El desarrollo sostenible como política en Colombia: un análisis crítico desde la protección de los páramos. (2020)
This article is intended to demonstrates how in the Colombian legal system, the existence of the principle of sustainable development implies an impact on the welfare of people. This relationship can also be considered tense in those cases of absolute prohibitions that prevent a real sustainable development in its social, economic and environmental dimensions. In order to show this reality, the authors analyze the legal status of páramo ecosystems in which, for the environmental protectionism, absolute restrictions are created in relation to the use of renewable natural resources and based on collective interest as a banner. The research findings evinced the tensions between the principle of sustainable development and rights due to erroneous interpretation and misapplication.